EFEKTIFITAS SENAM AEROBIC LOW IMPACT TERHADAP DISMENORE - Sherly " Yulita; Sri " Utami; Wasisto " Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   Dysmenorrhea is an excessive pain during menstruation caused by uncoordinated uterine contraction. There were some pain managements for dysmenorrhea, one of them was low impact aerobic gymnastic. This study aims to determine the effectiveness of low impact aerobic gymnastic to decrease the intensity of dysmenorrhea. The research design used in this study was “quasy experiment” with “non-equivalent control group” which was divided into an experimental group and control group. The sample in this research were the VII and VIII grade students of Junior High School 1 Gunung Toar, Kuantan Singingi district, the total sample were 31 students consist of 14 experimental group respondents and 17 control group respondents who taken by using purposive sampling techniques. The measuring instrument used was observation sheets. The analysis were univariate and bivariate analysis by using Mann-Whitney and Wilcoxon test. The result showed significant reduction of intensity of dysmenorrhea on experimental group after the group has given the low impact aerobic gymnastic with p value (0.001) < α (0.05). It means low impact aerobic gymnastic was effective to relieve the intensity of dysmenorrhea. The result of this study is expected to be an alternative to handling the dysmenorrhea for young women. Keywords: dysmenorrhea, menstruation, low impact aerobic gymnastic